2019
DOI: 10.1016/j.appet.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical-drift diffusion model of the roles of hunger, caloric density and valence in food selection

Abstract: Decisions based on affectively relevant stimuli, such as food items, hardly follow strictly rational rules. Being hungry, the food's caloric density, and the subjective valence attributed to various foods are known factors that modulate food choices. Yet, how these factors relatively and altogether contribute to the food choice process is still unknown. In this study, we showed 16 healthy young adults low-and high-calorie food when hungry or fed, and we asked them to evaluate the valence of each visually-prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Greater hunger during the satiety session led to less cautious decision-making and more errors on the information gathering task. Previous research had suggested that satiety could decrease information gathering, but the potential mechanism remained unclear [11,37]. Our results suggest that lingering hunger sensations after eating promote this impulsive tendency.…”
Section: Discussionmentioning
confidence: 54%
“…Greater hunger during the satiety session led to less cautious decision-making and more errors on the information gathering task. Previous research had suggested that satiety could decrease information gathering, but the potential mechanism remained unclear [11,37]. Our results suggest that lingering hunger sensations after eating promote this impulsive tendency.…”
Section: Discussionmentioning
confidence: 54%
“…On the one hand, there is the advantage of obtaining more reliable responses according to the particular context; on the other hand, it does not eliminate the influence of external variables that interfere in the evocation of the emotions, for example, the time of evaluation, to be satiated or with hunger. In online surveys, controlling the variability resulting from these factors is even more difficult and, according to Garlasco et al (2019), valence and arousal are permeated by satiety and hunger in food choices. Despite these shortcomings, the results evaluated in a laboratory setting and online are equivalent and proven, even with the difference in the control in the experimental conditions (Betella & Verschure, 2016), which leads us to believe that is possible to expand the use of the AS in sensory tasting conditions, providing similar results.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Decisions based on relatively affective stimuli, such as foods, are strongly influenced by modulators of food choices, such as hunger, caloric density of the food and subjective valence associated with the stimulus (Garlasco, Osimo, Rumiati, & Parma, 2019). Valence (pleasure–unpleasure) is a property of emotional stimuli that plays an important role in the diversity of human emotional experiences (Imbir, Jurkiewicz, Duda‐Goławska, & Żygierewicz, 2019) and, along with the degree of arousal (activation–deactivation), has a prominent effect on the emotional response of consumers (Jaeger et al, 2019; Pinto et al, 2020; Schouteten, Verwaeren, Lagast, Gellynck, & De Steur, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Meal size in humans is determined by innumerable factors related to the consumer, the food and the environment (Figure 1.). Therefore big data analytics, computational decision-making models (26) and correlation estimates of ingestive parameters with clinical and societal factors (70) may be extremely useful in revealing the role of different influencers on the organization of food intake (72,89).…”
Section: How To Define a Meal?mentioning
confidence: 99%